The 23rd International Electronic Conference on Synthetic Organic Chemistry 2019
DOI: 10.3390/ecsoc-23-06698
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effect of the Aqueous and Ethanolic Extracts of Annona Reticulate and Allium Sativumon Brine Shrimp Lethality Assay

Abstract: The present study was conducted to test for in vivo Brine Shrimp Lethality Assay (BSLA) of the Aqueous and ethanolic extracts Annona reticulate Linn. and Allium sativumand correlate cytotoxicity results with known pharmacological activities of the plants. Cytotoxicity was evaluated in terms of LC50 (lethality concentration). Ten nauplii were added into three replicates of each concentration of the plant extract. After 24 h the surviving brine shrimp larvae were counted and LC50 was assessed. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The results of this study agree with a previous report of the cytotoxicity of bulbs of Allium sativum alcoholic and aqueous extracts with LC50 values of 10.840 and 8.180 mg/mL against brine shrimps. 15 In cytotoxicity studies involving A. salina, it has been reported that LC50 values lower than 1000 ppm are considered cytotoxic (active) while non-toxic (inactive) if it is greater than 1000 ppm. 16 Results of this study (Table 3) indicate that all the plant extracts examined were cytotoxic.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study agree with a previous report of the cytotoxicity of bulbs of Allium sativum alcoholic and aqueous extracts with LC50 values of 10.840 and 8.180 mg/mL against brine shrimps. 15 In cytotoxicity studies involving A. salina, it has been reported that LC50 values lower than 1000 ppm are considered cytotoxic (active) while non-toxic (inactive) if it is greater than 1000 ppm. 16 Results of this study (Table 3) indicate that all the plant extracts examined were cytotoxic.…”
Section: Resultsmentioning
confidence: 99%